The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1994
DOI: 10.1016/s0022-5347(17)32602-2
|View full text |Cite
|
Sign up to set email alerts
|

Mortality of Patients after Radical Prostatectomy: Analysis of Recent Medicare Claims

Abstract: A 100% sample of Medicare claims records of patients undergoing radical prostatectomy in 1990 was analyzed for 30-day mortality and 1-year all-cause mortality rates. Overall, there was a 0.5% 30-day mortality and 1.8% 1-year mortality rate. Compared to the general population, mortality was approximately half of expected mortality and close to estimated mortality of elderly men in excellent health. There was no trend of increasing 30-day mortality with patient age, and a modestly increased 1-year mortality rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

1997
1997
2001
2001

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(14 citation statements)
references
References 6 publications
1
12
0
1
Order By: Relevance
“…A statistically significant number of patients had [1984][1985][1986][1987][1988][1989][1990] could reflect the experience of many urologie surgeons who were just beginning to perform radical prostatectomy, rather than the results of experi enced surgeons. In contrast, reports from individual sur geons or hospitals [3,4] and later statistics from US gov ernment agencies [7,8] show acceptably low early mor bidity and mortality. These data might reflect the growth in experience in radical prostatectomy that occurs in sin gle institutions [3].…”
Section: Introductionmentioning
confidence: 88%
“…A statistically significant number of patients had [1984][1985][1986][1987][1988][1989][1990] could reflect the experience of many urologie surgeons who were just beginning to perform radical prostatectomy, rather than the results of experi enced surgeons. In contrast, reports from individual sur geons or hospitals [3,4] and later statistics from US gov ernment agencies [7,8] show acceptably low early mor bidity and mortality. These data might reflect the growth in experience in radical prostatectomy that occurs in sin gle institutions [3].…”
Section: Introductionmentioning
confidence: 88%
“…This analysis assumes a peri-operative mortality rate of 0.3% which is consistent with published results of several series of radical prostatectomies 8,10,11 as well as a review of 100% of Medicare claims data. 12 The years of life lost (ie life expectancy) in the men who suffer peri-operative deaths (including both men with organ confined and nonorgan confined disease) are subtracted from the total number of years of life saved by screening.…”
Section: Methods the Screening Modelmentioning
confidence: 99%
“…This estimate is well supported by large, published series of RP and an analysis of 100% of Medicare data on patients who underwent RP. 12 However, other studies which have attempted to define the cost effectiveness of prostate cancer screening have used a peri-operative mortality rate of 1.1% based on older series of RP and incomplete Medicare data. 1,2 A surgical mortality rate of 1.1% in the present analysis would have resulted in an increase in the cost per life year saved of 0.88% for men aged 50 -69 screened with PSA and DRE, and 0.83% for men aged 50 -70 screened with PSA alone.…”
Section: Sensitivity Analysismentioning
confidence: 99%
“…In tors using the complete Medicare data base for 1990 observed a postoperative mortality rate of only 0.5%, a New York Medicare beneficiary population studied by Imperato et al 14 the rate of radical prostatectomy a figure much closer to those reported in the current study. 9 In another large series, Zincke et al reported in 1991 was 70% greater in white patients compared with African Americans. By 1993 this imbalance had 0.7% mortality within 30 days of surgery in 1123 patients treated at the Mayo Clinic.…”
Section: Discussionmentioning
confidence: 93%